Employee views of corporate tax aggressiveness in China: The effects of guanxi and audit independence - Taylor, Grantley; Fan, Ying Han; Tan, Y. (University of NSW, 2015)
This study examines the effects of guanxi and audit independence on the corporate tax aggressiveness of Chinese firms. Based on a survey completed by 174 respondents in 2013, we find that two types of guanxi: favour-seeking guanxi and rent-seeking guanxi are significantly associated with ethical judgments of corporate tax aggressiveness. Perceptions of audit independence in-fact are significantly negatively associated with these ethical judgments, whereas audit independence in-appearance is positively associated with them. Further, significantly positive associations exist between perceptions that tax-aggressive activities are good for the firm and its shareholders and favour-seeking guanxi and between these perceptions and stronger client-auditor relations. This study provides insights into the association between types of guanxi and the propensity of firm management to engage in corporate tax aggressiveness.